Factors associated with neuropsychiatric involvement in Latin American patients with systemic lupus erythematosus. (August 2021) - Barile-Fabris, Leonor A; Fragoso-Loyo, Hilda; Wojdyla, Daniel; Quintana, Rosana; Pons-Estel, Guillermo J; Catoggio, Luis J; García, Mercedes A; Saurit, Verónica; Drenkard, Cristina; Bonfa, Eloisa; Borba, Eduardo F; Sato, Emilia; et al.
Introduction: Factors related to presentation of neuropsychiatric (NP) SLE manifestations, early in the course of the disease, and during follow up have not been clearly established. Purpose: To identify disease and non-disease related factors associated with NP manifestations in early SLE. Methods: We included 1193 patients from the GLADEL inception cohort free of NP involvement at cohort entry. We evaluated the association of demographic, clinical and laboratory data with NP involvement during follow-up. Statistical methods: Independent factors associated with NP involvement were identified using a multivariable Cox regression model. Results: Factors independently associated with NP manifestations were: mestizo ethnicity (HR 1.701, 95% CI 1.282–2.258, p = 0.0002), myalgias/myositis (HR 1.832, 95% CI 1.335–2.515, p = 0.0002), pneumonitis (HR 2.476, 95% CI 1.085–5.648, p = 0.0312), shrinking lung (HR 2.428, 95% CI 1.074–5.493, p = 0.0331) and hemolytic anemia (HR 1.629, 95% CI 1.130–2.347, p = 0.0089). Longer disease duration at cohort entry (13 to 24 months) was associated with a lower risk of developing NP manifestations (HR 0.642, 95% CI 0.441–0.934, p = 0.0206). Conclusions: Patients with myalgias/myositis, pneumonitis, shrinking lung and hemolytic anemia are at higher risk of NP involvement, whereas longer disease duration at cohort entry is associated with a lower risk of developing NP involvement.